2006
DOI: 10.1007/s00421-006-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined lower body endurance and upper body resistance training improves performance and health parameters in healthy active elderly

Abstract: We investigated the effects of combined lower body (LB) endurance and upper body (UB) resistance training on endurance, strength, blood lipid profile and body composition in active older men. Ten healthy still active men (73+/-4 years, V(O2) peak: 36 (31-41) ml min-1 kg-1) were tested before and after 14 weeks of combined training (3 times week-1). Training consisted of 3x12 min of high intensity interval training on a bicycle for endurance interspersed by 3x12 min of UB resistance exercises. V(O2) peak during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 34 publications
(46 reference statements)
3
36
1
9
Order By: Relevance
“…While not unequivocal, it has been reported that aerobic training can improve muscle function in the elderly in the absence of muscle hypertrophy (1,13,21,53). Accordingly, we originally hypothesized that aerobic training would improve muscle function independent of changes in muscle mass by remodeling the contractile characteristics at the cellular level, which has been demonstrated in young competitive endurance athletes (19) and with endurance training in young subjects (36,47).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…While not unequivocal, it has been reported that aerobic training can improve muscle function in the elderly in the absence of muscle hypertrophy (1,13,21,53). Accordingly, we originally hypothesized that aerobic training would improve muscle function independent of changes in muscle mass by remodeling the contractile characteristics at the cellular level, which has been demonstrated in young competitive endurance athletes (19) and with endurance training in young subjects (36,47).…”
Section: Discussionmentioning
confidence: 98%
“…The large improvement in muscle mass was unexpected and is similar to results from our laboratory (46,49) and others (2,6,15) with regards to resistance exercise in similar subject populations. It has been suggested that aerobic exercise may help preserve muscle mass with advancing age (33,41); however, studies that have examined whole muscle size before and after training interventions have concluded that aerobic training does not alter size at the whole muscle level (11,13,23,38,39,53,54). A major confounding factor in many of those studies is that subjects experienced weight loss during the exercise intervention, which may limit the capacity for muscular growth (11,13,38,39,54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, alguns estudos mostraram diminuição na concentração de LDL-C (KAVANAGH, 2001;DUNCAN et al, 2003;VERNEY et al, 2006;HALVERSTADT et al, 2007;HELGE et al, 2007).…”
Section: As Terceiras Diretrizes Do National Cholesterol Education Prunclassified
“…Esse efeito deve-se, provavelmente, à redução do catabolismo da apolipoproteína A-I (HERBERT et al, 1984;THOMPSON et al, 1991) e a alterações da atividade de enzimas intracelulares e proteínas de transferência (BERG et al, 1994;DURSTINE, HASKELL, 1994). Após o treinamento físico, ocorre o aumento da atividade da LCAT (DUFAUX et al, 1986), da LLP (KIENS, LITHELL, 1989), a diminuição da atividade da LH (PELTONEN et al, 1981) e da CETP (TASKINEN, NIKKILA, 1981;SEIP et al, 1993 Muitos trabalhos mostraram diminuição do colesterol total plasmático em normolipidêmicos após algumas semanas de treinamento físico (OLCHAWA et al, 2004;LIPPI et al, 2006;VERNEY et al, 2006;HALVERSTADT et al, 2007;HELGE et al, 2007), enquanto em outros não houve alteração do colesterol total, tanto em indivíduos normolipidêmicos (PETRIDOU et al, 2005) quanto hipercolesterolêmicos (CROUSE et al, 1997). Em nosso trabalho o treinamento diminuiu o colesterol total nos hipercolesterolêmicos e não teve efeito sobre este parâmetro nos normolipidêmicos.…”
Section: Determinação Da Suscetibilidade Da Ldl à Oxidação (Lag Time)unclassified